Harmonization of Notary Office Law With ITE Law Related to Electronic Notary Protocol - Syarifa Yasmin Datau; Ranti Fauza Mayana; Muhamad Amirulloh (LEGAL BRIEF, 2023)
This article examines the implementation of the principle of legal certainty in the regulation of electronic notary protocols through harmonization of the UUJN with the ITE Law in the framework of digital transformation and what legal theory is most appropriate to use to renew the UUJN regarding the electronic notary protocol. The research method used is normative juridical using a statutory approach with descriptive analytical research specifications and qualitative juridical data analysis methods. Based on the results of the research, the implementation of the principle of legal certainty in the regulation of electronic Notary protocols through harmonization of the UUJN with the ITE Law has not been implemented properly, this can be initiated by specifically and formally accommodating the electronic Notary protocol in the UUJN when the electronic Notary protocol has been regulated in the UUJN then harmony with the ITE Law will be realized so that the principle of legal certainty can be realized. The most appropriate legal theory to use in the context of updating UUJN related to electronic notary protocols to provide more benefits to society 5.0 in the digital transformation era is Constitutional Theory, Developmental Law Theory, and Lex Informatica